2015
DOI: 10.1038/nclimate2643
|View full text |Cite
|
Sign up to set email alerts
|

Dual controls on carbon loss during drought in peatlands

Abstract: Peatlands store one-third of global soil carbon 1 . Drought/drainage coupled with climate warming present the main threat to these stores 1-4 . Hence, understanding drought e ects and inherent feedbacks related to peat decomposition has been a primary global challenge 5,6 . However, widely divergent results concerning drought in recent studies 3,7-11 challenge the accepted paradigm that waterlogging and associated anoxia are the overarching controls locking up carbon stored in peat. Here, by linking field and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
128
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 132 publications
(135 citation statements)
references
References 28 publications
6
128
0
1
Order By: Relevance
“…We further observed that the spectrophotometric slope coefficient S 250‐465 of WEOM, an index inversely related to the molecular weight and aromaticity of dissolved organic matter (Hansen et al., ), was greater under low water level and high graminoid cover. In accordance with other studies (Dieleman, Branfireun, & Lindo, ; Robroek et al., ; Wang, Richardson, & Ho, ), we interpret these results as evidence that the quality of WEOM was controlled by vascular plants, and especially by graminoids which released less aromatic C compounds presumably as root exudates (Crow & Wieder, ). Root exudates are indeed predominantly composed of simple labile C compounds, such as sugars (Gunina & Kuzyakov, ), easily available for microorganisms and easily respired as CO 2 (Werth & Kuzyakov, ).…”
Section: Discussionsupporting
confidence: 92%
“…We further observed that the spectrophotometric slope coefficient S 250‐465 of WEOM, an index inversely related to the molecular weight and aromaticity of dissolved organic matter (Hansen et al., ), was greater under low water level and high graminoid cover. In accordance with other studies (Dieleman, Branfireun, & Lindo, ; Robroek et al., ; Wang, Richardson, & Ho, ), we interpret these results as evidence that the quality of WEOM was controlled by vascular plants, and especially by graminoids which released less aromatic C compounds presumably as root exudates (Crow & Wieder, ). Root exudates are indeed predominantly composed of simple labile C compounds, such as sugars (Gunina & Kuzyakov, ), easily available for microorganisms and easily respired as CO 2 (Werth & Kuzyakov, ).…”
Section: Discussionsupporting
confidence: 92%
“…An additional explanation, which may be at least as important, involves the ubiquitous presence of shrubs throughout southeastern swamps. As mentioned above, the high polyphenol content of these shrubs and their litter, which becomes incorporated into peat, has been shown to retard decomposition under drought (Wang et al, ), which is fundamentally similar to drained conditions. These two factors, increased productivity and decreased decomposition, likely are responsible for carbon accumulation rates in CDR being similar to those of undisturbed forested peatland systems.…”
Section: Discussionmentioning
confidence: 98%
“…Most previously studied drought incubation experiments were relatively short-term manipulations, between several days and 1-2 months (Estop-Aragonés and Blodau, 2012; Fierer and Schimel, 2002;Venterink et al, 2002). In this experiment, we employed a 14-month drought, which is a rare but realistic event in our field situation, thus conducive to detecting an effect of long-term drought durations (Wang et al 2015). The strong temporal variations of NMR (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, the lowest and highest water levels occur in summer and winter, respectively. Throughout the year, groundwater levels rarely rise above ground surface and often reach 20 cm below the surface, but fall to over 100 cm in depth in the summer (Wang et al, 2015).…”
Section: Study Sitesmentioning
confidence: 99%